Maps of Charlotte County General Permit Trafficshed Channels and Secondary Channels - Robert A. Swett; David A. Fann; Elizabeth Staugler (EDIS)
This 33-page collection of maps depicts channels included in the Charlotte County General Permit (GP). Each map shows either channel segments within a GP trafficshed or segments in a GP secondary channel system. Written by Robert A. Swett, David A. Fann, and Elizabeth Staugler, and published on EDIS by Florida Sea Grant, July 2014.